Characterizations for several classes of alternative codes / Ngo Thi Hien - Ngo,Thi Hien
In this paper, we consider some new subclasses of alternative codes. In particular,characteristic properties and a hierachy of such codes are established also algorithms to test for these classes of codes are proposed